2020
DOI: 10.14745/ccdr.v46i04a06
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing: A powerful tool to address vaccine hesitancy

Abstract: According to the World Health Organization, vaccine hesitancy is among the top threats to global health and few effective strategies address this growing problem. In Canada, approximatively 20% of parents/caregivers are concerned about their children receiving vaccines. Trying to convince them by simply providing the facts about vaccination may backfire and make parents/caregivers even more hesitant. In this context, how can health care providers overcome the challenge of parental decision-making needs regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 15 publications
2
85
0
1
Order By: Relevance
“…However, our study has demonstrated that factors specific to the vaccine, perhaps more so than the disease are highly influential. Interventions recommended to improve maternal vaccination uptake have ranged from text reminders for prospective mothers to educational videos and motivational interviewing techniques for HCPs [ 110 112 ]. Based on the results of this review, interventions designed to impact maternal vaccine uptake should continue to encourage individualised HCP recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our study has demonstrated that factors specific to the vaccine, perhaps more so than the disease are highly influential. Interventions recommended to improve maternal vaccination uptake have ranged from text reminders for prospective mothers to educational videos and motivational interviewing techniques for HCPs [ 110 112 ]. Based on the results of this review, interventions designed to impact maternal vaccine uptake should continue to encourage individualised HCP recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal influenza vaccine was the most commonly investigated vaccine, either independently or as part of a study of factors influencing the uptake of multiple vaccines (63% of studies n = 75), followed by vaccines against pertussis (27% n = 32), pandemic influenza (24% n = 29), tetanus (8% n = 9), and antenatal vaccines generally (2% n = 2). We identified eight categories of factors that influence maternal vaccination across both qualitative and quantitative studies: accessibility and convenience (55 studies), personal values and lifestyle (43), awareness of information regarding the specific vaccine or disease of focus (90), social influences on vaccine use (109), emotions related to vaccination (85), perceptions of vaccine risk (110), perceptions of vaccine benefit (93), and personal vaccination history (80). From these eight categories, five could be synthesised quantitatively (Appendix p40-41 in S2 File).…”
Section: Plos Onementioning
confidence: 99%
“…Several strategies have been implemented in vaccination efforts over the past decades with variable levels of patient engagement and success. Across diverse patient populations, motivational interviewing as a patient-centered communication style has been an effective method of improving vaccination rates as the conversation is centered around the patient and provides a respectful and non-judgmental setting to explore possible concerns [ 24 ]. An additional benefit of motivational interviewing is that it further enhances the patient-doctor relationship, as poor rapport/connection has been demonstrated to negatively influence vaccination choice [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly cited interventions identified in the literature include presumptive language models, motivational interviewing, and educational dialogue-based interventions ( Ames, Glenton, & Lewin, 2017 ; Eller, Henrikson, & Opel, 2019 ; Harvey, Reissland, & Mason, 2015 ; Jacobson, St. Sauver, Griffin, MacLaughlin, & Finney Rutten, 2020 ; McClure et al, 2017 ; Salmon et al, 2015 ). Interventions based on information deficit models that assume misconceptions are due to a lack of knowledge—indicating that the solution is to provide more information—have been disproven to change the minds of VHC effectively and have even shown an increase in VH rates ( Gagneur, 2020 ; McClure et al, 2017 ; Salmon et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Current studies have reported that presumptive language models and motivational interviewing techniques are consistently the most effective interventions to address VH and increase vaccination rates ( Gagneur, 2020 ; Jacobson et al, 2020 ; McClure et al, 2017 ). When providers used the presumptive language model in vaccine discussions, it strengthened the recommendation by offering a matter-of-fact approach and shared confidence in the provider recommendation.…”
Section: Introductionmentioning
confidence: 99%